Penentuan burn up mutlak pelat elmen bakar U3Si2-Al tingkat muat uranium 2,96 gU/cm3pasca iradiasi - Aslina Br.Ginting; Yanlinastuti .; Noviarty .; Boybul .; Arif Nugroho; Dian Anggraini; Rosika Kriswarini (PTBN - BATAN, 2015)
Abstract Absolut burn-up determination of U3Si2-Al irradiated fuel plate with loading 2.96 gU/cm3. Absolute burn up measurement of U3Si2-Al irradiated fuel element with loading of 2.96 gU/cm3with RI-SIE 2 code has been done. The burn up calculation of U3Si2-Al irradiated fuel element is based on the content of 137 Cs, 235U and 239 Pu isotopes which is obtained by radiochemical analysis after an appropriate separation. The purpose of the separation a monitoring of the fission product (137 Cs isotope) and the heavy elements (uranium and plutonium) is to get the amount of 235U isotope accurately.Separation and analysis of 137Cs isotope had been done by cation exchange using zeolit Lampung and spectrometre-g. While the separation both of isotop 235U and 239Pu had been done by anion exchange column using Dowex 1 x 8 resin. The efluen of U in the column anion exchanger was eluted by using HNO3 8N and the efluent of Pu was eluted by HCl 0.1N + HF 0.036N. Both of isotopes were analyzed by using a spectrometre-a. The analysis result showed that the content of 137Cs isotope in U3Si2-Al irradiated fuel element was 0.000716 g/g sample, while the content of 235U, 239 Pu and 238 Pu were 0.032824 g/g sample, 0.000011g/g sample and 0.000005 g/g sample respectively. The result of measurement 235U isotope compared with initially content of isotop 235U (fabrication data) for being used in the absolute burn up measurement. The result of absolute burn up calculation of U3Si2-Al irradiated fuel U3Si2-Al with loading of 2.96 gU/cm3with RI-SIE 2 code was 51.69 %. Keyword : Separation and analysis of isotopes (Cs, U, Pu), cation and anion exchange, U3Si2-Al irradiated fuel element, burn up.. Abstrak Penentuan burn up mutlak pelat elemen bakar U3Si2-Al tingkat muat uranium 2,96 gU/cm3pasca iradiasi. Telah dilakukan perhitungan burn up mutlak bahan bakar PEB U3Si2-Al tingkat muat uranium (TMU) 2,96 gU/cm3 pasca iradiasi dengan kode RI-SIE 2. Perhitungan dilakukan melalui hasilpemisahan dan analisis isotop 137Cs isotop,235U,dan Pu di dalam PEB U3Si2-Al pasca iradiasi secara radiokimia. Tujuan pemisahan isotop hasil fisi khususnya isotop 137Cs dengan unsur heavy element (uranium dan plutonium) adalah untuk mendapatkan kandungan isotop 235U sisa (tidak terbakar) secara akurat. Pemungutan isotop 137Cs dilakukan dengan metode penukar kation menggunakan zeolit Lampung dan analisisnya menggunakan spektrometer-g, sedangkan pemungutan isotop 235U dan 239Pu dilakukan dengan metode kolom penukar anion menggunakan resin Dowex 1x8. Efluen U di dalam kolom dielusi menggunakan HNO3 8N dan efluen Pu dielusi dengan HCl 0,1N+HF 0,036N dan dianalisis menggunakan spektrometer-α.Hasil analisis menunjukkan bahwa kandungan isotop 137Cs di dalam PEB U3Si2-Al pasca iradiasi diperoleh sebesar 0,000716 g/g sampel, sedangkan kandungan isotop U dan Pu diperoleh masing-masing sebesar235U= 0,032824 g/g sampel, 239Pu= 0,000011g/g sampel dan 238Pu=0,000005 g/g sampel. Kandungan isotop 235U hasil pengukuran selanjutnya dibandingkan dengan kandungan isotop 235U mula-mula (data pabrikasi) untuk digunakan dalam perhitungan burn up mutlak. Hasil perhitungan burn up mutlak bahan bakar PEB U3Si2-Al TMU 2,96 gU/cm3 pasca iradiasi dengan kode RI-SIE 2 diperoleh sebesar 51,69 %. Kata kunci : Pemisahan dan analisis isotop (Cs, U, Pu), penukar kation dan anion, PEB U3Si2-Al pasca iradiasi, burn up.